Construction Service Company Value Chain Model at PT Bangunan Unik Lombok - Abdurrahman, Rio; Animah, Animah; Mariadi, Yusli (ARRUS Journal of Social Sciences and Humanities, 2023)
This study aims to identify, explain, and identify the appropriate value chain model for construction service companies. This research is conducted in PT. Bangunan Unik Lombok (BUL) that located in Sengkol Village, Grupuk Hamlet, Pujut District, Central Lombok Regency, West Nusa Tenggara Province. The type of research used is case study research, with descriptive data analysis methods and a quantitative approach. Based on the analysis that has been done at PT. BUL, as a whole PT. BUL had a fairly good value chain activity at the start of its operation. PT. BUL still needs to improve the performance of value chain activities to strengthen competition in the market and become a superior contractor, such as promoting and collaborating with government and private institutions, owning basic construction tools, project management and improving internal and external business. This research suggests that companies should make more use of and maintain every factor or activity that influences the success of a construction company. Maintain good relations with existing clients and try to build relationships and collaboration with prospective clients and government or private institutions. Implement and adhere to existing activity procedures. Paying attention to efficiency and effectiveness in producing construction products.